Omentin-1 mitigates non-alcoholic fatty liver disease by preserving autophagy through AMPKα/mTOR signaling pathway - Ziqing Huang; Linfei Luo; Zhihua Xiao; Ming Xiong; Zhili Wen (Scientific Reports)
Abstract Adipose tissue-derived adipokines facilitate inter-organ communication between adipose tissue and other organs. Omentin-1, an adipokine, has been implicated in the regulation of glucose and insulin metabolism. However, limited knowledge exists regarding the regulatory impact of endogenous omentin-1 on hepatic steatosis. C57BL/6J mice were fed with high-fat diet (HFD) for 8 weeks to induce nonalcoholic fatty liver disease (NAFLD), while HepG2 cells were exposed to a 0.1 mM free fatty acid (FFA) mixture for 24 h to induce hepatic steatosis. Both the mice and cells were treated with omentin-1, and the therapeutic effects as well as the underlying molecular mechanisms were investigated. Our data demonstrate that omentin-1 attenuates weight and fat mass gain, preserves glucose homeostasis, normalizes the expression of lipogenesis-related proteins, and alleviates hepatic lipid accumulation in HFD fed mice. Furthermore, omentin-1 normalized AMPKα/mTOR signaling and preserves autophagy in these mice. In vitro, omentin-1 also preserves autophagy and attenuates lipid accumulation by normalizing AMPKα/mTOR signaling in a cell model of FFA treated HepG2 cells. However, inhibition of AMPK with Compound C or AMPKα whole-body knockout reverses the above beneficial effects of omentin-1. The present study demonstrates that omentin-1 exerts a preventive effect on non-alcoholic fatty liver disease (NAFLD) by preserving autophagy through normalizing the AMPKα/mTOR pathway, thereby suggesting its potential as a promising therapeutic agent against NAFLD.